(untitled) - Reed, W. Maxwell (New York, 1960)
The Stars For Sam is a story of the dramatic changes the earth, its plants, and animals have undergine over millions of years.
Keywords: Geology,Paleontology,Địa chất,Cô sinh vật học; Juvenile literature,Juvenile literature,Trẻ vị thành niên,Trẻ vị thành niên